The Amazonian mangrove systems accumulate and release dissolved neodymium and hafnium to the oceans - Xu, Antao; Hathorne, Ed; Seidel, Michael; Liu, Te; Asp Neto, Nils Edvin; Koschinsky-Fritsche, Andrea; Dittmar, Thorsten; Frank, Martin (Communications earth & environment, 2025)
Mangroves are essential tropical ecosystems nurturing a wide range of marine biodiversity and counteracting global warming by sequestering atmospheric carbon dioxide. Hence, the export mechanisms and fluxes of particulate and dissolved organic carbon and trace elements from mangroves directly influence coastal productivity, the global carbon cycle and thus global climate, which are, however, not well constrained. Here we find consistent radiogenic neodymium and hafnium isotopic compositions of porewater, sedimentary iron-manganese oxyhydroxides and coastal seawater, suggesting that the Amazonian mangrove belt supplies trace elements through porewater discharge, dissolution of iron-manganese oxyhydroxides and their interactions with seawater. Together, these processes supply 8.4 × 106 g yr-1 dissolved neodymium, equivalent to 64% of the total sources of neodymium to the Amazonian coastal seawater. Globally, mangrove systems along the continental margins contribute 6-9% of the net neodymium input to the ocean, which is similar to the contributions from atmospheric deposition. A contribution of this magnitude is potentially also the case for other trace elements, given the strong correlations between neodymium and iron (Pearson r = 0.92), and manganese (r = 0.75) concentrations across the entire river-ocean section, emphasizing the crucial role of mangrove system inputs in micro-nutrient cycling.